The Role and Therapeutic Value of Syndecan-1 in Cancer Metastasis and Drug Resistance - Guo, Sen; Wu, XinYi; Lei, Ting; Zhong, Rui; Wang, YiRan; Zhang, Liang; Zhao, QingYi; Huang, Yan; Shi, Yin; Wu, Luyi (Frontiers in Cell and Developmental Biology, 2022)
Abstract: Metastasis and relapse are major causes of cancer-related fatalities. The elucidation of relevant pathomechanisms and adoption of appropriate countermeasures are thus crucial for the development of clinical strategies that inhibit malignancy progression as well as metastasis. An integral component of the extracellular matrix, the type 1 transmembrane glycoprotein syndecan-1 (SDC-1) binds cytokines and growth factors involved in tumor microenvironment modulation. Alterations in its localization have been implicated in both cancer metastasis and drug resistance. In this review, available data regarding the structural characteristics, shedding process, and nuclear translocation of SDC-1 are detailed with the aim of highlighting strategies directly targeting SDC-1 as well as SDC-1-mediated carcinogenesis.